ANALISIS KEMACETAN LALU LINTAS DI RUAS JALAN PROF. DR. H. ALOE SABOE KOTA GORONTALO (STUDI KASUS RUAS JALAN PASAR MOODU) - Pobela, Dira Sucilya; Akbar, La Ode Juni (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2022)
The city of Gorontalo is an area that has the potential to develop and compete with other regions, one of which is in terms of development in the field of transportation, especially regarding land transportation. The road is a means of transportation that is very important for human survival. On several roads in Gorontalo the ability to walk is still very limited, one of which is on Jalan Prof. Dr. H. Aloe Saboe Gorontalo City (precisely on the Moodu market road section where every Monday there is always a weekly market which causes congestion on the road, considering that Monday is a busy day. That's why the author took the research title "Traffic Congestion Analysis in Jalan Prof. Dr. H. Aloe Saboe, City of Gorontalo (Case study of the Pasar Moodu road section). To find out the side barriers and the level of road service on Jalan Prof. Dr. H. Aloe Saboe, primary data and secondary data are needed. The primary data needed are traffic volume data, road geometric data, side friction survey and instantaneous speed survey, while the secondary data needed is population data in the city of Gorontalo. Based on the results of the analysis, the free flow speed is obtained on the Prof. Dr. H road section. .Aloe Saboe worth 29.48 km/hour, rated capacity of 1930.1 pcu/hour, side resistance of 421 events/hour included in the category of sed side resistance ang(M), and the level of road service is in category B, which means that the flow is still stable with moderate traffic volume and speed is starting to be limited by traffic conditions, low density and internal traffic barriers have not affected speed.